Prediction of Equilibrium Mixing Index and Optimum Mixing Time for Three solid materials in Fluidized Column - Sulaymon, Abbas H.; Abbas, Ammar S.; Salman, Rasha H. (Al-Khwarizmi Engineering Journal, 2010)
Equilibrium and rate of mixing of free flowing solid materials are found using gas fluidized bed. The solid materials were sand (size 0.7 mm), sugar (size0.7 mm) and 15% cast iron used as a tracer. The fluidizing gas was air with velocity ranged from 0.45-0.65 m/s while the mixing time was up to 10 minutes. The mixing index for each experiment was calculated by averaging the results of 10 samples taken from different radial and axial positions in fluidized QVF column 150 mm ID and 900 mm height. The experimental results were used in solving a mathematical model of mixing rate and mixing index at an equilibrium proposed by Rose. The results show that mixing index increases with increasing air velocity and mixing time until it reaches an optimum value then decrease to an equilibrium value. The results also show the dependency of the mixing index on the particle size of the tracer component. The statistical analysis of the obtained theoretical mixing index versus the experimental mixing index shows that the standard error is 0.92 % (about 1 %) with the correlation coefficient of 0.9857 and the total residual of 0.002 for the ninth observation of the mixing index (theoretical versus experimental) over 95% confidence level.